Ascite-solid model of prostate cancer and its morphological characteristics - E. A. Plotnikova; N. B. Morozova; A. V. Ryabova; G. V. Trunova; V. A. Khokhlova; V. B. Loschenov; A. A. Pankratov; A. D. Kaprin (Сибирский онкологический журнал, 2023)
Targeted therapy and immunotherapy are considered promising novel therapies capable of increasing the effcacy of prostate cancer (PCa) treatment. The purpose of the study was to obtain and characterize TRAMP-C2 subcutaneous and ascite-solid models of prostate cancer in C57Bl/6j mice to study specifc anti-tumor activity of the candidate molecules of targeted drugs and adjust immunotherapy strategies in an evidence-based manner. Material and Methods. We used cultured TRAMP-C2 cells in subcutaneous and ascites mouse prostate cancer models. Histological and immunohistochemical methods were used to study the tumor tissues. Results. The high in vivo growth ability of TRAMP-C2 cells was demonstrated in subcutaneous and intraperitoneal inoculation of C57Bl/6j mice. These tumors are characterized by a high reproducibility and level of PSMA expression. Histological study showed that subcutaneous and carcinomatous TRAMP-C2 tumor nodules had solid structure morphologically corresponding to low differentiated neoplasm, cytomorphological analysis of smears showed that peritoneal fuid containd a large number of rounded tumor cells, macrophages and erythrocytes. Conclusion. The obtained subcutaneous and ascite-solid models of TRAMP-C2 can be useful for the development of new ways to effectively treat cancer, including targeted and immunotherapy, as well as for the experimental study of biotherapeutic effects using PSMA as a target, and photoinduced effects.